2019
DOI: 10.3390/sym12010031
|View full text |Cite
|
Sign up to set email alerts
|

Super Stability of Ag Nanoparticle in Crystalline Lamellar (Lc) Liquid Crystal Matrix at Different pH Environment

Abstract: The symmetry concept in this paper is related to the natural self-assembly of noble metal nanoparticles in the long range periodic structure of liquid crystal (LC). The current study deliberates the effect of pH on the stability of nanoparticles (NPs) in the lamellar phase of a lyotropic LC environment. The LC was prepared by the mass ratio 0.33:0.22:0.45 for (HDTABr):1-pentanol:water. The LC containing silver nanoparticles (AgNPs) was prepared by replacing the water with Ag solution. The AgNPs were produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The results showed that the catalytic difference between the anionic dye MO and the cationic dye MB was caused by the negative potential of Ag NPs on the surface of the catalyst Fe 3 O 4 @PDA@Ag. 35 For the cationic dye MB, the electrostatic attraction between the materials can make MB quickly accumulate on the surface of Ag NPs, which promoted the catalytic reaction and accelerated the catalytic rate of Fe 3 O 4 @PDA@Ag on MB.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the catalytic difference between the anionic dye MO and the cationic dye MB was caused by the negative potential of Ag NPs on the surface of the catalyst Fe 3 O 4 @PDA@Ag. 35 For the cationic dye MB, the electrostatic attraction between the materials can make MB quickly accumulate on the surface of Ag NPs, which promoted the catalytic reaction and accelerated the catalytic rate of Fe 3 O 4 @PDA@Ag on MB.…”
Section: Resultsmentioning
confidence: 99%